Cross-Cultural Investigation of Male Gait Perception in Relation to Physical Strength and Speed - Fink, Bernhard; Wübker, Marieke; Ostner, Julia; Butovskaya, Marina L.; Mezentseva, Anna; Muñoz-Reyes, José Antonio; Sela, Yael; Shackelford, Todd K. (Frontiers in Psychology, 2017)
Previous research documents that men and women can accurately judge male physical strength from gait, but also that the sexes differ in attractiveness judgements of strong and weak male walkers. Women’s (but not men’s) attractiveness assessments of strong male walkers are higher than for weak male walkers. Here, we extend this research to assessments of strong and weak male walkers in Chile, Germany, and Russia. Men and women judged videos of virtual characters, animated with the walk movements of motion-captured men, on strength and attractiveness. In two countries (Germany and Russia), these videos were additionally presented at 70% (slower) and 130% (faster) of their original speed. Stronger walkers were judged to be stronger and more attractive than weak walkers, and this effect was independent of country (but not sex). Women tended to provide higher attractiveness judgements to strong walkers, and men tended to provide higher attractiveness judgements to weak walkers. In addition, German and Russian participants rated strong walkers most attractive at slow and fast speed. Thus, across countries men and women can assess male strength from gait, although they tended to differ in attractiveness assessments of strong and weak male walkers. Attractiveness assessments of male gait may be influenced by society-specific emphasis on male physical strength.